Curtailing Job Insecurity and Counterproductive Work Behaviours as Bullying Effects in Pakistani Academia: Work Engagement as a Moderator - Fatima Ashraf; Muhammad Asif Khan (National University of Modern Languages (NUML), Islamabad, 2021)
Judging from persistent changes, drive for performance and widespread uncertainty that characterize the Pakistani higher education system, this study sought to confirm whether workplace bullying - a by-product of relentless change - triggers job insecurity and counterproductive work behaviours in the bullied faculty, and whether these damaging outcomes are moderated by work engagement. Using convenience sampling, we sought data from 337 faculty members from the higher education sector. Analysis confirmed that bullying triggers job insecurity and counterproductive work behaviours while mixed findings emerged for the hypothesized moderation effects of work engagement. The study mainly stresses infusing work engagement within a work environment where bullying prevails. Managers may design jobs to augment engagement in a pressurized work environment with an aim to curtail job insecurity and counterproductive work behaviours for sustained performance in a changing work environment.